Use of NHFOV vs. NIPPV for the respiratory support of preterm newborns after extubation: A meta-analysis - Mei, Zhaojun; Ming, Li; Wu, Zhifeng; Zhu, Yong (Frontiers in Pediatrics, 2023)
Objectives: This meta-analysis evaluated and compared the efficacy and safety of noninvasive high-frequency oscillatory ventilation (NHFOV) and nasal intermittent positive-pressure ventilation (NIPPV) for use with newborns. Methods: We searched the PubMed, Cochrane Library, EMBASE, Web of Science, CNKI, Wanfang and VIP databases from inception to August 28, 2022. Randomized controlled trials (RCTs) that evaluated and compared the efficacy and safety of NHFOV and NIPPV in newborns were included in the review and meta-analysis, which followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting guidelines. Results: Twelve articles (thirteen trials) involving 2,030 patients were included. There was not significantly difference in the intubation rates (RR = 0.58, 95% CI 0.29, 1.16, P = 0.12) and the reintubation rates (RR = 0.70, 95% CI 0.45, 1.06, P = 0.09) between NHFOV versus NIPPV. Compared with NIPPV, NHFOV could decrease the duration of non-invasive ventilation (standard mean difference (SMD) = -1.40, 95%CI -2.22, -0.59, P = 0.0007) and the risk of BPD (RR = 0.84, 95%CI 0.73, 0.97, P = 0.02). However, all included studies had a high risk of bias, and the overall quality of the evidence for the outcomes was low or very low. Conclusion: In our study, the reduction of reintubation rates and intubation rates tended to favor NHFOV over NIPPV, although these results did not reach statistical significance. Furthermore, NHFOV seems to reduce the incidence of BPD without increasing other complications. Nevertheless, definite recommendations cannot be made based on the quality of the published evidence.